Decisions, choice and shared decision making in antenatal clinics: An observational study. Issue 9 (September 2015) - Garrard, Francesca; Ridd, Matthew; Narayan, Harini; Montgomery, Alan A.
Highlights SDM and choice have been prioritised in UK maternity services. However, no choice was offered in 75% of antenatal decisions. Choice was associated with the decision made, consultation length and doctor seniority. Without choice, patients and healthcare professionals can't truly share decisions. We need to understand the factors that impact choice availability.